2018
DOI: 10.1155/2018/5940748
|View full text |Cite
|
Sign up to set email alerts
|

Swim Training Modulates Skeletal Muscle Energy Metabolism, Oxidative Stress, and Mitochondrial Cholesterol Content in Amyotrophic Lateral Sclerosis Mice

Abstract: Recently, in terms of amyotrophic lateral sclerosis (ALS), much attention has been paid to the cell structures formed by the mitochondria and the endoplasmic reticulum membranes (MAMs) that are involved in the regulation of Ca2+ signaling, mitochondrial bioenergetics, apoptosis, and oxidative stress. We assumed that remodeling of these structures via swim training may accompany the prolongation of the ALS lifespan. In the present study, we used transgenic mice with the G93A hmSOD1 gene mutation. We examined mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 55 publications
4
54
0
Order By: Relevance
“…Deforges et al [15] documented that swim training delays the onset of the first symptoms of the disease, sustains the motor function, and increases the life span of ALS mice by about 25 days. Similar results were obtained in our recent studies [36]. In contrast to running exercise, large-scale motoneurons are activated by swimming.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Deforges et al [15] documented that swim training delays the onset of the first symptoms of the disease, sustains the motor function, and increases the life span of ALS mice by about 25 days. Similar results were obtained in our recent studies [36]. In contrast to running exercise, large-scale motoneurons are activated by swimming.…”
Section: Introductionsupporting
confidence: 92%
“…Decrease in oxidative stress seems to be one of the most important strategies for treating ALS disease and other neuromuscular disorders [32,33,34]. Regulation of metal homeostasis and decrease in oxidative stress, similar to the benefits of swim training, leads to the prolongation of the lifespan of transgenic mice [35,36]. Deforges et al [15] documented that swim training delays the onset of the first symptoms of the disease, sustains the motor function, and increases the life span of ALS mice by about 25 days.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies evaluated the correlation between oxidative stress and exercise in ALS. Among them, Flis et al (2018) demonstrated that a swimming training is able to extend the lifespan of ALS G93A mice. The transgenic mice performed an exercise protocol that started at the presymptomatic stage (70 days of age) and ended when the mice were 115 days of age.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Although preclinical studies (Flis et al, 2018;Just-Borràs et al, 2019) suggest that swimming and aquatic training could be very encouraging exercise interventions in ALS, clinical studies are needed to translate these mouse exercise results to humans, considering also that personalized aquatic training programs will be needed.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…One such gene therapy candidate is caveolin-1 (Cav-1), a MLR scaffolding protein that organizes NTRs (Trk) and neurotransmitter receptor signaling complexes in MLRs [12][13][14]. Both pre-clinical and clinical findings revealed that Cav-1 and Cav-1 associated signaling complexes (NTRs and neurotransmitter receptors) were decreased in degenerating neurons in AD, chronic traumatic encephalopathy (CTE), and amyotrophic lateral sclerosis (ALS) [15][16][17][18]. In contrast, we previously showed that neuron-targeted Cav-1 over-expression (i.e., synapsin-promoted Cav-1 or SynCav1) augmented agonist-mediated synaptic signaling (e.g., NTRs, neurotransmitter receptors) and dendritic arborization in vitro [12], preserved MLR-localized TrkB and extended life span in ALS mice [19], suggesting that alterations in Cav-1 expression affects pro-survival signaling and neuroprotection in neurodegenerative conditions .…”
Section: Introductionmentioning
confidence: 99%